2009
DOI: 10.1037/a0017294
|View full text |Cite
|
Sign up to set email alerts
|

Substance use and the paradox of good and bad attentional bias.

Abstract: Habitual substance use is associated with attentional bias for stimuli related to the use. The current study tested whether individuals' substance use can be predicted from their attentional bias for concern-related and substance-related stimuli. Participants (N = 71; 54% male) were selected among university students and the community. The study was conducted in Iran, in which alcohol consumption is illegal. Participants completed a substance use questionnaire and classic, substance-, and concern-related Stroo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…This questionnaire measures the frequency of using nonprescribed substances, including sedatives, antidepressant agents, anti-anxiety drugs, analgesic agents, psychedelic herbal medicines, tea and coffee, nicotine (i.e., smoking tobacco), and energizing and hallucinating drugs, among the Iranian population. University students were asked to rate their frequency of using substances on a Likert scale from 0 = not at all to 6 = quite often during the past 3 months (Fadardi, Ziaee, & Shamloo, 2009). For the purposes of the current study, individual and total frequency of substance use was used.…”
Section: Instrumentsmentioning
confidence: 99%
“…This questionnaire measures the frequency of using nonprescribed substances, including sedatives, antidepressant agents, anti-anxiety drugs, analgesic agents, psychedelic herbal medicines, tea and coffee, nicotine (i.e., smoking tobacco), and energizing and hallucinating drugs, among the Iranian population. University students were asked to rate their frequency of using substances on a Likert scale from 0 = not at all to 6 = quite often during the past 3 months (Fadardi, Ziaee, & Shamloo, 2009). For the purposes of the current study, individual and total frequency of substance use was used.…”
Section: Instrumentsmentioning
confidence: 99%
“…Two unpublished studies 43,44 found that Iranian heroin and opium abusers had greater attentional bias for drug-related stimuli than non-abusers. Another published study 45 showed that drug-related attentional bias was inversely related to attentional bias for personally relevant goals; that is, as distraction for stimuli related to participants' personal (non-substance-related) goals increased, distractions for drug-related stimuli decreased. Studies from South Korea that used eye-tracking techniques 46,47 found that smokers had an attentional bias for smokingrelated cues.…”
Section: Variants Of the Attention Control Training Programmentioning
confidence: 99%
“…A Persian computerized version (Fadardi et al 2009) adapted from original word-color Stroop test (Stroop 1935), was used to evaluate one particular aspect of executive function, inhibition (Sibley and Beilock 2007). The task was a manual color response task in which the participants were asked to identify the print color of the stimuli.…”
Section: Stroop Color-word Test (Scwt)mentioning
confidence: 99%